Analisis Regresi Spasial Persentase Kemiskinan di Kawasan Timur Indonesia Tahun 2022 - Huda, Achmad Choirul; Az-Zahra, Afifah; Yasmin, Fatia Putri; Ningrum, Icha Wahyu Kusuma; Putra, Wildhan Surya; Budiasih, Budiasih (Politeknik Statistika STIS, 2023)
Poverty is a multidimensional problem that occurs in Indonesia. Poverty is closely related to the level of food security in an area. Eastern Indonesia is a concern because of the high poverty rate. The purpose of this research is to look at the constituent variables of food security that have a significant effect on the percentage of poverty at the regency/city level in Eastern Indonesia. The spatial heterogeneity identification carried out shows that the use of the Geographically Weighted Regression (GWR) model is better than multiple linear regression to show the relationship between the variables constituting food security and the percentage of poverty. A local GWR model was generated to see spatial heterogeneity at the regency/city level with a focus on the variable per capita normative consumption ratio (NCPR), the percentage of households with a proportion of food expenditure of more than 65% of income (PP), and its combination with other variables. It was found that the poverty rate at the regency/city level in Eastern Indonesia is influenced by different constituent variables of food security, especially between PP variables with access to electricity and life expectancy.